Electrophysiological channel interactions using focused multipolar stimulation for cochlear implants. (24th September 2015) - George, Shefin S; Shivdasani, Mohit N; Wise, Andrew K; Shepherd, Robert K; Fallon, James B
Abstract: Objective . Speech intelligibility with existing multichannel cochlear implants (CIs) is thought to be limited by poor spatial selectivity and interactions between CI channels caused by overlapping activation with monopolar (MP) stimulation. Our previous studies have shown that focused multipolar (FMP) and tripolar (TP) stimulation produce more restricted neural activation in the inferior colliculus (IC), compared to MP stimulation. Approach . This study explored interactions in the IC produced by simultaneous stimulation of two CI channels. We recorded multi-unit neural activity in the IC of anaesthetized cats with normal and severely degenerated spiral ganglion neuron populations in response to FMP, TP and MP stimulation from a 14 channel CI. Stimuli were applied to a 'fixed' CI channel, chosen toward the middle of the cochlear electrode array, and the effects of simultaneously stimulating a more apical 'test' CI channel were measured as a function of spatial separation between the two stimulation channels and stimulus level of the fixed channel. Channel interactions were quantified by changes in neural responses and IC threshold (i.e., threshold shift) elicited by simultaneous stimulation of two CI channels, compared to stimulation of the test channel alone. Main results . Channel interactions were significantly lower for FMP and TP than for MP stimulation ( p  < 0.001), whereas no significant difference was observed between FMP and TP stimulation. With MP stimulation, threshold shifts increased with decreased inter-electrode spacing and increased stimulus levels of the fixed channel. For FMP and TP stimulation, channel interactions were found to be similar for different inter-electrode spacing and stimulus levels of the fixed channel. Significance . The present study demonstrates how the degree of channel interactions in a CI can be controlled using stimulation configurations such as FMP and TP; such knowledge is essential in enhancing CI function in complex acoustic environments.